KARAKTERISTIK PEMAMPATAN TANAH RESIDU DI TPA RATAHAN - Assa, Vicky A.; Sompie, O. B.A.; Lintong, E (Sam Ratulangi University, 2016)
AbstractSoil residues are the result of physical and chemical weathering of the rocks beneath its formation occurred over rocks came from, so there are some specific characteristics of the type of soil residues are not in accordance with the basic concepts of soil mechanics are generally prepared by the behavior of alluvial soil . The ground color is yellowish brown residue . Overview Ratahan case in landfill sites are on sloping native land , therefore the compression on the type of soil residues need more in-depth review of the determination of the parameters of consolidationThe test sample soil residue undisturbed were taken to the Laboratory of Soil Test, Department of Civil Engineering, Polytechnic of Manado for testing the water content, test weight content, test weight type, test Atterberg limits, test seepage and testing consolidation by using the tool oedometer standard. The test results were analyzed further consolidation, so that unknown behavior of soil residue compression. The results of calculations using the tool oedometer consolidation parameters in landfill Ratahan, the voltage value preconsolidation by Casagrande method is 1.20 kg / cm2 sedangan method